Prevalence of attention deficit hyperactivity symptoms in female schoolchildren in Saudi Arabia - Elham Jenahi; Mohamed S. Khalil; Hassan Bella (Annals of Saudi Medicine, 2012)
BACKGROUND AND OBJECTIVES: Attention deficit hyperactivity disorder (ADHD) is the most commonly seen developmental disorder, with significant impacts on the child’s social, psychological, and scholastic functioning. The aim of this study was to determine the prevalence and sociodemographic correlates of ADHD in female primary schoolchildren. DESIGN AND SETTING: A cross-sectional study conducted in Al-Khobar Town, Eastern Saudi Arabia. METHODS: A random sample of six primary schools for girls was chosen, from which samples of 1009 students were selected by systematic random sampling, with ages ranging between 6 and 15 years (mean and standard deviation, 9.2 [1.9]). All subjects were screened for different types of ADHD using the Attention Deficit Disorders Evaluation Scale. RESULTS: The overall prevalence of ADHD was 3.5%. The prevalence of children with ADHD/inattentive type was 2.1% and the prevalence of children with ADHD/hyperactive-impulsive type was 5.6%. This rate decreased significantly with increase in age. The prevalence was higher in government school students, among Saudi citizens, later born siblings, higher number of siblings, and lower parental education. CONCLUSIONS: It was concluded that the prevalence of ADHD in female primary schoolchildren is comparable with what has been reported in other studies. Some demographic factors should be taken into consideration when interpreting this result. Implications and recommendations to the concerned authorities are outlined to improve the health and educational care services to help these children.